THE VALIDITY OF HOTS ASSESSMENT INSTRUMENT ON CELL SUBJECT FOR STUDENT IN GRADE XI - Marlina Marlina; Rahmawati Rarussyamsu; Ristiono Ristiono; Elsa Yuniarti (Universitas Islam Negeri Ar-Raniry, 2021)
Learning success is known through assessment. The 2013 Curriculum Assessment emphasizes assessments that train students to be able to Higher Order Thinking Skills (HOTS). HOTS capabilities according to Bloom's taxonomy include the ability to analyze, evaluate, and create. The results of observations note that students' HOTS ability is still lacking and the availability of HOTS assessment instruments for cell material used as guidelines is not yet available. One way to train students' HOTS is to develop an instrument of higher order thinking skills on cell material. This research is a 4D model development research, which is define, design, development, and dissemination. The research subjects consisted of 2 lecturers majoring in Biology FMIPA UNP. The object is assessment instrument HOTS on cell material. The results showed that the assessment instrument had an average value of 89.23% validity with valid criteria. The assessment instruments were developed based on aspects of material, construction, language, and higher order thinking skills. To be conclude, assessment instrument has valid and can be used to measure and train HOTS students, especially cell material.